The Garhwal by-election : report of a fact-finding committee - Ahmed, Bashiruddin (Citizens for Democracy, 1981)
Report on alleged corrupt practices at the 1981 by-election in a vacant Lok Sabha Seat, Garhwal Constituency, Uttar Pradesh.